Correction: Review of the synthesis, transfer, characterization and growth mechanisms of single and multilayer graphene. Issue 45 (30th May 2017) - Lee, H. Cheun; Liu, Wei-Wen; Chai, Siang-Piao; Mohamed, Abdul Rahman; Aziz, Azizan; Khe, Cheng-Seong; Hidayah, N. M. S.; Hashim, U.
Abstract : Correction for 'Review of the synthesis, transfer, characterization and growth mechanisms of single and multilayer graphene' by H. Cheun Lee et al., RSC Adv., 2017, 7, 15644–15693.